Professional Socialisation of Early Career Secondary School Teachers in Tanzania - Peter, Levina Peter; Maro, Wadrine Maro; Nzima, Ibrahimu Nzima (Papers in Education and Development, 2022)
This paper presents the findings of a study on how early career teachers (ECTs) socialise and cope with their teaching roles. It focuses on ECTs ' professional needs and socialisation strategies. Data were collected from 18 participants selected purposefully from two district education offices and four secondary schools. In-depth interviews and thematic analysis techniques were respectively used to generate and analyse data. Findings revealed that, in Tanzania, ECTs need induction, mentoring, collaborative work environment and development of compentences in instructional planning and teaching approaches. In professional socialisation process, ECTs are engaged in self-directed professional development, extra-time teaching hours and computer aided instruction. It is recommended that ECTs should be provided with more professional and social support to make them cope with contextual factors and become effective in accommodating teaching and other professional responsibilities in schools. Keywords: community of practice, early career teacher, professional development, teacher retention,teacher socialisation